Myanmar Agricultural Performance Survey Round One: Note on Sample Characteristics and Weighting - Myanmar Agriculture Policy Support Activity (International Food Policy Research Institute, 2023)
The first round of the Myanmar Agricultural Performance Survey (MAPS)–a nationwide phone panel consisting of 3,893 households–was implemented between February 2022 and March 2022. The objective of the survey was to collect data on farm characteristics and agricultural assets, area and crops planted, access to inputs, crop marketing, and constraints in agricultural activities. The respondents interviewed are a sub-sample of the Myanmar Household Welfare Survey (MWHS) and was purposely selected from a large phone database aimed at being representative at the national, region/state and urban/rural levels in Myanmar. In this paper, we discuss the steps taken to ensure that the MAPS is nationally and sub-nationally representative at the state/region and urban/rural level.